Turnitin peer feedback: controversial vs. non-controversial essays - Mohammed Abdullah Alharbi; Ali H. Al-Hoorie (International Journal of Educational Technology in Higher Education, 2020)
Abstract Although an important goal of learner peer feedback is promoting critical thinking, little attention has been paid to the nature of the topic, particularly whether it is controversial. In this article, we report on a study where 52 English majors were asked to comment on essays written by their peers using the PeerMark module of Turnitin. Half of the essays were about controversial topics in the Saudi society (e.g., women driving and banning cigarettes), whereas the other half were less controversial (e.g., importance of sleep and respecting parents). Our results showed that the participants provided significantly more critical, global comments on controversial essays. At the same time, this increase in global comments did not come at the expense of local, language-related comments—in that the participants did not provide significantly fewer language comments on controversial essays. The participants also reported favorable attitudes toward this task due to the convenience and anonymity of online feedback, thus allowing them to express their opinions more freely on controversial topics. We therefore concluded that utilizing an online platform that permits double-blind peer review on controversial essays seems to have to the potential to stimulate critical thinking among language learners.